Computational modeling of therapies related to cognitive vulnerability and coping - Ab. Aziz, Azizi; A. Klein, Michel C. (IOS Press, 2011)
Due to recent research, the neurobiological elements behind mental disorders such as depression become more and more clear. This paper presents an integrated computational model based on neurobiological insights and psychological theories.The model is used to analyse the effect of existing psychological treatments. The simulation experiments give an insight in the interaction between different cognitive components in mental disorders and illustrates why different treatments can have different effects for people with different genetic dispositions.